Study of interactions between hyaluronan and cationic surfactants by means of calorimetry, turbidimetry, potentiometry and conductometry - Krouská, J; Pekař, M; Klučáková, M; Šarac, B; Bešter-Rogač, M (Carbohydrate polymers, 2017)
The thermodynamics of the micelle formation of the cationic surfactants tetradecyltrimethylammonium bromide (TTAB) and cetyltrimethylammonium bromide (CTAB) with and without the addition of hyaluronan of two molecular weights was studied in aqueous solution by titration calorimetry. Macroscopic phase separation, which was detected by calorimetry and also by conductometry, occurs when charges on the surfactant and hyaluronan are balanced. In contrast, turbidimetry and potentiometry showed hyaluronan-surfactant interactions at very low surfactant concentrations. The observed differences between systems prepared with CTAB and TTAB indicate that besides the electrostatic interactions, which probably predominate, hydrophobic effects also play a significant role in hyaluronan interactions with cationic surfactants.
Keywords: CTAB; Polyelectrolyte-surfactant interactions; Hyaluronan; Surfactants; TTAB